Síntese e caracterização de filme biodegrável oriundo de amido de ariá (Goeppertia allouia) modificado fisicamente - Santos, Maria Gabriele Meirellis dos (Brasil, 2023)
The pollution caused by the accumulation of plastic waste has become an aggravating factor due to inadequate management of the approximately 12 billion tons of plastic waste expected to be transferred or disposed of in the environment by the year 2050. An alternative to this problem is the production of bioplastics from natural sources such as starch because of its biodegradable character and low economic cost. Ariá starch has been the target of research recently at the Federal University of Amazonas. However, native starch generally has low properties. To improve starch properties, physical modification of starch is used, for the low cost, time and because it is considered a green technique. Therefore, the present work aimed to verify the possibility of creating biofilms based on modified starch via ultrasound and compare with films based on native starch. The starch was modified for 30 minutes and 60 minutes by ultrasound technique and characterized by the Technique of Microscopic Scanning Electronics (SEM) to investigate the modification in the granules, by thermal analysis of Thermogravimetry and Explotatory Differential Calorimetry (TG/DSC), the starch structure was performed by the Ray Diffraction - X (XRD) technique and fourier transform infrared spectroscopy (FTIR) was used to verify the functional groups. The study verified that it was possible to obtain film based on native ariá starch and modified, the films were characterized by (SEM), Moisture, Thickness and solubility. It was possible to verify that the film modified by ultrasound at 30 minutes presented better homogeneity, greater transparency. The films based on ariá starch showed low solubility and high humidity. In addition, the films presented thickness below 1 mm.